Power flow tracing method via GUI - Ahmad Khudri Shamsuddin (2023)
Renewal in electrical engineering is greatly appreciated in an ever-expanding era. In electrical engineering, there are various simulations used. Each simulation has its own ability to solve various electrical problems. Therefore, the necessity of power flow tracing becomes one of the simulations which can also improve efficiency in the electrical system. Two simulations that have been used to trace power flow which are Power World simulation and MATLAB. Both methods are very popular in electrical engineering. In this thesis, power tracing results obtained from Microsoft Excel involving Power World are used to be user-friendly. It was found that the power flow tracing method via Graphical User Interface (GUI) assessed using Visual Basic for Application (VBA) on Microsoft Excel. In addition, the analysis performed enables to make a comparison and validate the results from this project with the results based on the research paper, thus a new simulation on power flow tracing is proposed in this thesis.